(untitled) (Journal of School Administration Research and Development, 2022)
The pandemic has exacerbated teacher attrition in California with 88% of the hiring demand in high needs areas of education (Darling-Hammond et al., 2018). The shortage of credentialed teachers has increased the need to fill positions with intern teachers who have limited or no teaching experience. This is most prevalent in special education, mathematics, and science. Many intern teachers will leave the profession within the first two to five years of service. The impact will take its toll on the students with the greatest needs. This study explored the support and training needs of intern teachers in high need areas; critical components support systems needed to recruit, retain, and increase intern teacher longevity; and the existing systems of support for the intern teacher’s success and retention. The findings may assist school administrators and university faculty in designing support systems for preparing, coaching, and supporting intern teachers to ensure their success in the profession.